Employment Termination Dispute Between Airline and Flight Attendant: A Legal Analysis of Industrial Relations in The Aviation Sector - Sugeng; Kintan R. Virdauzy; Indra L. Nainggolan (KRTHA BHAYANGKARA, 2025)
Termination of employment (PHK) represents one of the most complex and frequent forms of industrial disputes, particularly in the aviation industry, a sector that demands strict adherence to professionalism standards, including physical appearance and presentation. This study aims to analyze the employment termination dispute between PT Garuda Indonesia and Bhonita Sary (former flight attendant) based on Decision Number 134/Pdt.Sus-PHI/2018/PN Srg. This research employs a normative juridical method with a statutory approach and court decision analysis, focusing on the interpretation of employment contracts and the application of labor regulations.  The findings reveal that the basis for the termination was the flight attendant's non-compliance with weight requirements, which was considered a breach of the employment agreement, particularly concerning service standards and corporate image. Although the company had provided the employee with an opportunity to adjust her weight according to the stipulated standards, differing interpretations of the contract clauses became the primary factor leading to the dispute.  In its considerations, the panel of judges declared the termination legally valid, referring to the dispute resolution procedures that had been conducted in accordance with Law Number 2 of 2004 on the Settlement of Industrial Relations Disputes. This decision underscores the importance of legal certainty and compliance with employment contracts but also opens a critical discourse on balancing the company's right to regulate work standards with the worker’s right to fair labor protection.